A study on factors influencing the effectiveness of training at Iskandar Regional Development Authority (IRDA) / Najiha Nasri and Nur Hidayah Ibrahim - Nasri, Najiha; Ibrahim, Nur Hidayah (Faculty of Business and Management, 2014)
Training refers to the programs designed to help employee improve their knowledge and skills in the workplace successfully. In addition, they include the formal ongoing efforts of corporations and other organization to improve the performance and self-fulfilment of their employees through a variety of methods and programs. This attempts to identify significant determinants of training effectiveness. By constructing the hypothetical research model to investigate the effect of the training environment, work environment and types of training (independent variable) towards training effectiveness (dependent variable), a survey questionnaire were distributed to employees at Iskandar Regional development Authority (IRDA) who have attended training programs. A Likert-type scale has been developed and tested in this study. The results of the research were obtained by using Pearson correlation and multiple regressions.